2009
DOI: 10.1007/s10571-009-9404-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Voltage-Dependent Sodium Channels in the Process of Synaptogenesis During the Postnatal Cortical Development of Rats

Abstract: The developmental changes of the sodium channel and construction of synapse connection were studied in cerebral cortical pyramidal neurons of rats at different age groups. We used whole-cell patch-clamp recordings to characterize electrophysiological properties of cortical neurons at different age stages, including the sodium currents, APs evoked by depolarizing current and short-term plasticity of the eEPSCs. The result shows that the sodium currents undergo a hyperpolarizing shift in activation process and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…(Kim and Park 2009). Consistent to our previous study on pyramidal cells (Wang et al 2009), many LTS interneurons younger than P7 did not give all five responses, even the first response was not induced either. This phenomenon indicated that, in early age stage (P \ 7), the developmental changes of both the pyramidal cells and interneurons embodied in the intrinsic parameters of individual neuron primarily such as sodium channel increases, size augment and enhancement of excitability.…”
Section: Developmental Changes Of Stimulus-evoked Excitatory Postsynasupporting
confidence: 91%
See 4 more Smart Citations
“…(Kim and Park 2009). Consistent to our previous study on pyramidal cells (Wang et al 2009), many LTS interneurons younger than P7 did not give all five responses, even the first response was not induced either. This phenomenon indicated that, in early age stage (P \ 7), the developmental changes of both the pyramidal cells and interneurons embodied in the intrinsic parameters of individual neuron primarily such as sodium channel increases, size augment and enhancement of excitability.…”
Section: Developmental Changes Of Stimulus-evoked Excitatory Postsynasupporting
confidence: 91%
“…Previous studies presented that pyramidal cells showed significant intrinsic changes in almost postnatal 2-3 weeks in the somatosensory cortex (Wang et al 2009) and in PFC (Zhang 2004), while LTS interneurons in the PFC exhibited a developmental delay in the process of maturation, which were in accordance with the other reports about the maturation of the GABAergic signaling systems (Douglas and Martin 2009). During the early postnatal period, maybe the development of LTS interneurons directly depends on the growth of excitatory pyramidal cells.…”
Section: Maturation Properties Of Lts Interneurons In Pfc During Postsupporting
confidence: 86%
See 3 more Smart Citations